Analysis of natural dyestuffs in Achillea grandifolia Friv. using HPLC-DAD and Q-TOF LC/MS - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2017)
The aim of this study was to analysis of natural dyestuffs from Achillea grandifolia Friv. leaves, flowers and stems in wool dyeing. The optimum dye extraction temperature and time were determined by spectrophotometrically. Natural dyeing was carried out with the optimized dye extract on unmordanted wool fabrics. The dyestuffs were analysed using electrospray ionization-quadrupole-time of flight liquid chromatography mass spectrometry (ESI-Q-TOF LC/MS) and high-performance liquid chromatography equipped with photodiode array detector (HPLC-DAD) methods. Thus, the purpose of this study was to identify and quantify of colouring constituents from the plant. As a result of the analysis, natural dyestuffs in Achillea grandifolia were determined as luteolin, rutin, quercetin, luteolin-7-0 glucoside, quercetagetin 3,6-dimethyl ether, chlorogenic acid, caffeic acid, dicaffeoylquinic acid and their isomers. Finally, the colorimetric properties of the dyed fabrics were evaluated in CIELAB (Commission Internationale de l'Eclairage, CIE) system. L* (brightness), a* (red/green) and b* (yellow/blue) values of dyestuffs were measured.
Keywords: Natural dyestuffs; HPLC-DAD; Achillea grandifolia Friv; PERFORMANCE LIQUID-CHROMATOGRAPHY; PHENOLIC-ACIDS; L.; QUANTIFICATION; IDENTIFICATION; FLAVONOIDS; EXTRACTION; COTTON; DYE